Effect of Ion Magnetron Sputtering Method on Scanning Electron Microscopy (SEM)Images of Materials with Different Surface Properties - ZHANG Jie, ZOU Junwen, LIU Xueguang, LI Xiaoying (Cailiao Baohu)
In order to investigate the effect of ion magnetron sputtering parameters on the scanning electron microscopy (SEM) images of nonconductive materials with different surface properties， the advantages and limitations of various ion magnetron sputtering conditions， including target material， sputtering time and sputtering cycles were studied， along with their applicable ranges.Results showed that the gold target exhibited good continuity with large grain nucleation of gold.Due to its high sputtering energy， it easily caused thermal loss on the sample surface， and the gold grains adhered to the surface.Therefore， gold targets were found to be suitable for low -magnification SEM imaging(<10 000) and materials with a certain surface hardness.In contrast， the platinum target showed poor continuity with small platinum grain nucleation and lower sputtering energy.It was more likely to embed into the sample surface， forming a morphological framework， making it suitable for high-magnification SEM imaging (>30 000) and most non-conductive materials.Using a method of fewer， multiple ion magnetron sputtering cycles， reducing the sputtering cycles appropriately not only weakened the effect of the gold film on the material’s morphology and structure but also helped conserve resources and protect the environment.This result provides experimental guidance for researchers to scientifically and accurately analyze SEM images of samples.